KEMITRAAN KEHUTANAN SEBAGAI RESOLUSI KONFLIK TENURIAL DI LAHAN KONSESI PT RESTORASI EKOSISTEM - Gusti Ayulia Mustika Weni; Indra Gumay Febryano; Hari Kaskoyo; Irwan Sukri Banuwa (Forestry Study Program University Of Mataram, 2020)
Forestry partnership is a social forestry scheme as an attempt resolution of conflict society and permit holders. The objective of the research to explain the forestry partnership program conducted by PT REKI and the people of Dusun Kunangan Jaya I. This research used a qualitative research approach. The methods of data collection include in-depth interviews, participant observation, and document studies. The results of the research showed a forestry partnership carried out by PT REKI and KTH Berkah Jaya, KTH Bungin Mandiri and indigenous people of Batin Sembilan. The agroforestry pattern is applied to partnership lands. The percentage of forestry partnership outcomes, 85% for the community and 15% for PT REKI. The rights and obligations that have not been achieved have an impact on hampering agroforestry management. The limited funding of PT REKI, which depends on donors as a source of income causing the forestry partnership program has not been maximized. PT REKI in supporting forestry partnership provides various facilities including the provision of forestry plant seeds, cattle, education, and health services community empowerment. The rejection of forestry partnership cooperation carried out by most of the community because of mismatch between the expectation of community and PT REKI. The performance of the government in forest monitoring needs to be improved to support forestry partnerships to cut down land conflicts while improving community welfare.Forestry partnership is a social forestry scheme as an attempt resolution of conflict society and permit holders. The objective of the research to explain the forestry partnership program conducted by PT REKI and the people of Dusun Kunangan Jaya I. This research used a qualitative research approach. The methods of data collection include in-depth interviews, participant observation and document studies. The results of the research showed a forestry partnership carried out by PT REKI and KTH Berkah Jaya, KTH Bungin Mandiri and indigenous people of Batin Sembilan. The agroforestry pattern is applied to partnership lands. The percentage of forestry partnership outcomes, 85% for the community and 15% for PT REKI. The rights and obligations that have not been achieved have an impact on hampering agroforestry management. The limited funding of PT REKI, which depend on donors as a source of income causing the forestry partnership program has not been maximized. PT REKI in supporting forestry partnership provides various facilities including the provision of forestry plant seeds, cattle, education and health services community empowerment. The rejection of forestry partnership cooperation carried out by most of the community because of mismatch between the expectation of community and PT REKI. The performance of the government in forest monitoring needs to be improved to support forestry partnership to cut down land conflicts while improving community welfare.